Thrombin Generation Measured Ex Vivo Following Microvasculor Injury Is Increased in SLE Patients with Antiphospholipid-protein Antibodies - Musiał, Jacek; Swadźba, Jakub; Jankowski, Miłosz; Grzywacz, Marek; Bazan-Socha, Stanisława; Szczeklik, Andrzej (Thrombosis and Haemostasis, 1997)
Antiphospholipid-protein antibodies (APA) include lupus-type anticoagulant (LA) and antibodies recognizing complexes of anionic phospholipids (e.g. cardiolipin) and proteins (e.g. prothrombin and (β2-glycoprotein I). The presence of APA is associated with an increased risk of both arterial and venous thrombosis. However, the pathogenic mechanism leading to thrombosis in patients with APA remains unclear. We studied 32 patients with systemic lupus erythematosus (SLE) who were divided into two groups depending on the presence (n = 19) or absence (n = 13) of APA. Healthy volunteers (n = 12) matched by age and sex served as controls. In all subjects LA and IgG class anticardiolipin antibodies (ACA) were determined. Thrombin generation was monitored ex vivo measuring fibrinopeptide A (FPA) and prothrombin fragment F1 + 2 (F1 + 2) in blood emerging from a skin microvasculature injury, collected at 30 second intervals. In subjects with antiphospholipid antibodies mean FPA and F1 + 2 concentrations were signiF1cantly higher at most blood sampling times than in controls. In some SLE patients with APA the process of thrombin generation was clearly disturbed and very high concentrations of F1brinopeptide A were detected already in the F1rst samples collected. Two minutes after skin incision SLE patients without APA produced slightly more FPA, but not F1 + 2, as compared to healthy subjects. Mathematical model applied to analyze the thrombin generation kinetics revealed that APA patients generated signiF1cantly greater amounts of thrombin than healthy controls (p = 0.02 for either marker). In contrast, in the same patients generation of thrombin in recalciF1ed plasma in vitro was delayed pointing to the role of endothelium in the phenomenon studied. In summary, these data show for the F1rst time that in SLE patients with antiphospholipid-protein antibodies thrombin generation after small blood vessel injury is markedly increased. Enhanced thrombin generation might explain thrombotic tendency observed in these patients.